New radioimmunoadsorbent method for detection of hepatitis B surface antigen. - Moore, R P (1982)
A radioimmunoadsorbent assay for the detection of hepatitis B surface antigen (HBsAG) is described. The method uses small DEAE-cellulose columns to adsorb HBsAg from serum or plasma samples, and it uses 125 I-labeled antibody to HBsAg to detect the adsorbed antigen. A single 2-h incubation at 45 degrees C is used in the procedure. The sensitivity of the method was determined with the Bureau of Biologics HBsAg reference panels and was shown to be equivalent to other third-generation test methods. The specificity of the method was evaluated by testing specimens from blood donors, dialysis patients, and hospital staff in parallel with commercial radioimmunoassay kits for HBsAg. In the tests performed on 2,868 blood donor specimens, 6 positive specimens were identified by both the radioimmunoadsorbent method and the commercial radioimmunoassay kits. These positive specimens were confirmed by a counterimmunoelectrophoresis procedure. One nonconfirmable, repeatably positive specimen was observed with the radioimmunoadsorbent method. In testing 1,250 specimens from dialysis patients and hospital staff, 120 confirmable positive specimens were identified by both the radioimmunoadsorbent method and a commercial test. Overall, the false positive rate for the radioimmunoadsorbent method was found to be less than 1%.